Efficacy and safety of repellents marketed in Brazil against bites from Aedes aegypti and Aedes albopictus: A systematic review - Gomes Fernandes, Maria Raquel [UNESP]; Cruz Lopes, Luciane; Suguimoto Iwami, Rodrigo; Del Grossi Paglia, Mariana; Mateus de Castilho, Bruna [UNESP]; Maicon de Oliveira, Alan; Fulone, Izabela; Silveira Leite, Ricardo; de Cássia Bergamaschi, Cristiane (Elsevier, 2021)
Background: Dengue, Zika and Chikungunya viruses represent a serious public health problem. No evidence is available on the efficacy of repellents commercially available in Brazil. This systematic review assessed the efficacy and safety of products containing repellents commercially available in Brazil for protection against bites from Aedes aegypti and Aedes albopictus. Methods: We performed a systematic review using the CENTRAL, MEDLINE, EMBASE, CINAHL, Web of Science, AMED, LILACS and Scopus databases. Randomized clinical trials and non-randomized clinical trials comparing topical repellent products registered with the Brazilian Health Surveillance Agency were included. Main outcomes of interest investigated were adverse effects, percentage repellency and protection time against bites. Pairs of reviewers selected the studies, extracted the data and evaluated the risk of bias. Results: Sixteen studies were included. No adverse effects were reported by the studies. Against Ae. aegypti: protection time using DEET (10% and 20%-spray) was similar to IR3535 (10% and 20%-spray) and longer than citronella (5%-spray). DEET (25%-solution) had longer protection time than eucalyptus (25%-solution), while DEET (20%-lotion) had longer protection time than citronella (10%-lotion). There was no difference in protection time between herbal repellents. DEET (7% and 15%- spray) had higher percentage repellency compared to both icaridin (7%-spray) and IR3535 (20%-spray). Against Ae. albopictus: DEET (15%-spray) had a similar protection time to icaridin (20%-spray), but longer than citronella (10%-spray). Conclusion: DEET proved more effective than the other synthetic and natural repellents marketed in Brazil for protecting against bites from the mosquito species investigated. All repellents studied exhibited satisfactory safety profile.
Keywords: Chikungunya; Dengue; Efficacy; Insect repellents; Safety; Zika